Front cover: Resveratrol Improves Muscle Atrophy by Modulating Mitochondrial Quality Control in STZ‐Induced Diabetic Mice. Issue 9 (4th May 2018) - Wang, Dongtao; Sun, Huili; Song, Gaofeng; Yang, Yajun; Zou, Xiaohu; Han, Pengxun; Li, Shunmin
Abstract : Mol. Nutr. Food Res. 2018, 62, 1700941 DOI:10.1002/mnfr.201700941 Resveratrol (RSV), a natural antioxidant found mainly in grape skin, exerts potential protective properties on muscle atrophy, but the evidence is lacking in diabetes mellitus (DM). In article number1700941, Dongtao Wang, Shunmin Li, and co‐workers find that RSV improves muscle atrophy and physical activity by increasing mitochondrial biogenesis, suppressing the activation of mitophagy, and reducing mitochondrial fission and fusion in streptozocin (STZ)‐induced DM mice.